Estimating the Potential for Rooftop Generation of Solar Energy in an Urban Context Using High-Resolution Open Access Geospatial Data: A Case Study of the City of Tromsø, Norway - Gareth Rees; Liliia Hebryn-Baidy; Clara Good (ISPRS International Journal of Geo-Information)
An increasing trend towards the installation of photovoltaic (PV) solar energy generation capacity is driven by several factors including the desire for greater energy independence and, especially, the desire to decarbonize industrial economies. While large ‘solar farms’ can be installed in relatively open areas, urban environments also offer scope for significant energy generation, although the heterogeneous nature of the surface of the urban fabric complicates the task of forming an area-wide view of this potential. In this study, we investigate the potential offered by publicly available airborne LiDAR data, augmented using data from OpenStreetMap (OSM), to estimate rooftop PV generation capacities from individual buildings and regionalized across an entire small city. We focus on the island of Tromsøya in the city of Tromsø, Norway, which is located north (69.6° N) of the Arctic Circle, covers about 13.8 km2, and has a population of approximately 42,800. A total of 16,377 buildings were analyzed. Local PV generation potential was estimated between 120 and 180 kWh m−2 per year for suitable roof areas, with a total estimated generation potential of approximately 200 GWh per year, or approximately 30% of the city’s current total consumption. Regional averages within the city show significant variations in potential energy generation, highlighting the importance of roof orientation and building density, and suggesting that rooftop PV could play a much more substantial role in local energy supply than is commonly assumed at such high latitudes. The analysis method developed here is rapid, relatively simple, and easily adaptable to other locations.